The Role of Audit Quality in Moderating Audit Tenure, Audit Fees, Auditor’s Reputation and Audit Committees on the Integrity of Financial Statements - Slamet Wahyudi; Sabaruddin Sabaruddin (Ridwan Institute, 2023)
Research Aims: This study aims to empirically prove the effect of factors such as Audit Tenure, Audit Fee, Auditor’s Reputation and Audit Committee on the Integrity of Financial Statements which is moderated by Audit Quality. Companies that are the object of research are banking companies listed on the Indonesia Stock Exchange in the observation period from 2014 to 2022. Design/Methodology/Approach: The research sample used 20 banking companies listed on the Indonesia Stock Exchange which were taken based on a purposive sampling technique. Research analysis uses Logistic Regression with Moderating Regression Analysis. Research Finding: Based on the analysis of research results using Logistic Regression with Moderating Regression Analysis (MRA) it can be concluded that Tenure Audits do not have a significant influence on the integrity of financial statements. Audit Fee has no significant influence on the integrity of financial statements. Auditor's reputation has a significant positive effect on the integrity of financial statements. The audit committee has a significant positive influence on the integrity of financial statements. Audit quality has not been able to moderate the influence of tenure audits on the integrity of financial statements. Audit quality has not been able to moderate audit fees on the integrity of financial statements. Audit quality is positively and significantly able to moderate the effect of auditor's reputation on the integrity of financial statements. Audit quality is positively and significantly able to moderate the influence of the audit committee on the integrity of financial statements. Theoretical contribution/Originality: The results of this study can be used as a contribution to Agency Theory.